Observations of fragments of cometary nuclei in the atmosphere over Kiev - K. I. Churyumov; A. F. Steklov; A. P. Vidmachenko; G. N. Dashkiev (Вісник Астрономічної школи, 2015)
As a result of two years of observations the authors identified twilight class of bolides. Unlike the nighttime observations of bright meteor traces that can be seen no more than ten seconds, twilight traces are observed from a few minutes to two hours. The paper considers the synchronous observation of the evening twilight fireball in the sky over Kiev 25/06/2014 by Dashkiev G.N. and Steklov A.F. The basic distance between of photographing points was 8,55 km. On the assumption that the explosions of large meteoroids in the atmosphere and flash of brightness occurs at the height of their maximum braking in the range significantly less than the height of the homogeneous atmosphere, it follows that the thermal explosion of the meteoroid took place at the height substantially more than 15 km. Moreover, flashings and disintegration of perhaps cometary material, began at height more than 25 km. The meteoroid does not flown to the surface of the Earth and disintegrated into fine particles. Preliminary estimate of initial mass of the fragment before the entry into the atmosphere is from 2 to 10 tons. On both photos are visible only dispersed trace of cometary nuclei fragments that disintegrated.